PENGARUH BRAND AWARENESS, BRAND ASSOCIATION DAN BRAND LOYALTY SHOPEE TERHADAP KEPUTUSAN PEMBELIAN DI KOTA BATAM: PENGARUH BRAND AWARENESS, BRAND ASSOCIATION DAN BRAND LOYALTY SHOPEE TERHADAP KEPUTUSAN PEMBELIAN DI KOTA BATAM - Wati, Riana; Husein, Alice Erni (LPPM Universitas Putera Batam, 2025)
Shopping through electronic commerce is one of the new methods that are growing rapidly in the current era. Many e-commerce companies provide similar services because e-commerce has an important role in building strong brand equity in the eyes of consumers and displaying the value of the products or services offered. The purpose of this research is to analyse the effect of Shopee brand equity on consumer purchasing decisions in Batam City. This research study uses a quantitative approach. The data testing methods used in this research study are validity test, reliability test, classical assumption test, multiple linear regression test, determination coefficient test, and hypothesis testing. The data was obtained through distributing structured questionnaires online to 111 respondents representing various age segments, gender, and region of residence. The results of this study indicate that brand awareness, brand association and brand loyalty have a significant effect on consumer purchasing decisions. The coefficient of determination test results show that brand awareness, brand association and brand loyalty have a significant effect on purchasing decisions by 81.2% while the rest is influenced by other variables not examined in this study. Keywords: Brand Awareness; Brand Association; Brand Loyalty; Purchasing Decision